If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 91x = 39x + 12 Reorder the terms: 4 + 91x = 12 + 39x Solving 4 + 91x = 12 + 39x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-39x' to each side of the equation. 4 + 91x + -39x = 12 + 39x + -39x Combine like terms: 91x + -39x = 52x 4 + 52x = 12 + 39x + -39x Combine like terms: 39x + -39x = 0 4 + 52x = 12 + 0 4 + 52x = 12 Add '-4' to each side of the equation. 4 + -4 + 52x = 12 + -4 Combine like terms: 4 + -4 = 0 0 + 52x = 12 + -4 52x = 12 + -4 Combine like terms: 12 + -4 = 8 52x = 8 Divide each side by '52'. x = 0.1538461538 Simplifying x = 0.1538461538
| (x+2)(x+5)=18 | | (3v-6)/3v | | .5(x+30)+1.1x=79 | | -(-2a-3)-5=-3(a-6) | | c^2d^2-4cd+4=0 | | -4(x+1)=-1(x+5) | | a^6-7a+a-7=0 | | 3(25-b)+b=35 | | x^3-7x^2+6=0 | | -2-(-8)-7+3= | | 9x^2-20x+2=0 | | -4k-(3-7k)=15 | | 4b-6b+7=9 | | 7=5c+22-10c | | 2w-7w+3=-22 | | 46=4x-4+6x | | -7w-(w+4)=12 | | 5(x-2)+3=-3(2x+1)-6 | | 7m+20-10=-25 | | 36r^2-60r+25=0 | | 15y-(-5y+36)=24 | | 12+x+9=37 | | x^2-6x-y^2+7=0 | | -98y^2-26=0 | | x+15+19=41 | | 40x+35y=720 | | 9aq^4-9an^4=0 | | 4y-(2y+2)=18 | | 21+20+x=70 | | 6/6-5/6 | | 49x^2-490x+697+16y^2+128y=0 | | k^3+20k^2+100k=0 |